Finite Element Modelling of Shock Wave Propagation Over Obstacles - Soukup, Josef; Klimenda, František; Skočilas, Jan; Žmindák, Milan (Manufacturing Technology Journal, 2019)
The current software allows to simulate the behavior of the technical objects on the pressure wave of detonation fumes, the spread of the air and the action on the construction, and on the people. It is possible to simulate the changed conditions and their effect on objects without that it would be necessary to make costly and time consuming tests. Modeling of the pressure wave belongs to the fluid flow interference and obstacles in the flow. This paper aims to develop simulation models based on the finite element method for the elasto-plastic wave propagation from the explosion of a spherical explosive. First, it is analyzing the propagation of pressure waves at a contact explosion with a perfectly rigid surface, which represents the face of the earth. Then it analyzed explosion contact with deformable surface. Finally, it is investigated propagation of pressure waves through the ditches around the perpendicular wall.
Keywords: Pressure wave; Shock wave; TNT